Common Childhood Viruses and Pubertal Timing: The LEGACY Girls Study - McDonald, Jasmine A (Am J Epidemiol, 2020)
Earlier pubertal development is only partially explained by childhood body mass index; the role of other factors, such as childhood infections, is less understood. Using data from the LEGACY Girls Study (North America, 2011–2016), we prospectively examined the associations between childhood viral infections (cytomegalovirus (CMV), Epstein-Barr virus (EBV), herpes simplex virus (HSV) 1, HSV2) and pubertal timing. We measured exposures based on seropositivity in premenarcheal girls (n = 490). Breast and pubic hair development were classified based on mother-reported Tanner Stage (TS) (TS2(+) compared with TS1), adjusting for age, body mass index, and sociodemographic factors. The average age at first blood draw was 9.8 years (standard deviation, 1.9 years). The prevalences were 31% CMV(+), 37% EBV(+), 14% HSV1(+), 0.4% HSV2(+), and 16% for both CMV(+)/EBV(+) coinfection. CMV(+) infection without coinfection was associated with developing breasts an average of 7 months earlier (hazard ratio (HR) = 2.12, 95% confidence interval (CI): 1.32, 3.40). CMV infection without coinfection and HSV1 and/or HSV2 infection were associated with developing pubic hair 9 months later (HR = 0.41, 95% CI: 0.24, 0.71, and HR = 0.42, 95% CI: 0.22, 0.81, respectively). Infection was not associated with menarche. If replicated in larger cohorts with blood collection prior to any breast development, this study supports the hypothesis that childhood infections might play a role in altering pubertal timing.